Pengembangan FIDTI (Fluid Isomorphic Diagnostic Test Inventory) Sebagai Instrumen Diagnostik Miskonsepsi Fluida - Mohammad Zaky Tatsar; Nuril Munfaridah; Markus Diantoro (Universitas Sebelas Maret, 2017)
Abstract: We have developed a FIDTI (Fluid Isomorphic Diagnostic Test Inventory) as misconception diagnostic instruments. This development research is based on the importance of educators knowing the misconceptions of learners. Beside that the accurate quantity of diagnostic tests to help learners and educators understand the misconceptions that occur in the fluid material is still small.The model that used in this research FIDTI development is ADDIE (Analysis, Design, Development, Implementation, and Evaluation) development model. We use four steps of ADDIE development model. Four of these stages are deemed to be sufficiently adapted to the circumstances and eligibility. The product of this research is diagnostic assessment instrument of multiple choice which has four options with only one option is true and the other options are false. The options of products are developed based on student answer at essay question that has done before the product was developed. The products consist of 9 isomorphics that one isomorphic is consisting of three questions presented in a different form, but finished with the same concept (isomorphic). The number of indicators and subject topics which have respectively developed have 44,4% and 53,6% more than the previsiouse research. FIDTI is suitable to diagnostie student misconseption’s about fluids with validity test scores of 3,6 from 4. Diagnostic conception product in the study is using two criterias. Based on analysis data, the mean accuracy of the first criteria and the accuracy of the second criteria are 73,8% and 68,9%. Abstrak: Telah dilakukan penelitian pengembangan FIDTI (Fluid Isomorphic Diagnostik Test Inventory) sebagai instrumen diagnostik miskonsepsi fluida. Penelitian pengembangan ini didasarkan pada pentingnya pendidik mengetahui miskonsepsi peserta didik serta kuantitas tes diagnostik yang akurat untuk membantu peserta didik dan pendidik dalam memahami miskonsepsi yang terjadi pada materi fluida masih sedikit. Adapun model yang digunakan dalam penelitian pengembangan FIDTI adalah model pengembangan ADDIE (Analysis, Design, Development, Implementation, dan Evaluation). Produk yang dikembangkan merupakan instrumen penilaian diagnostik dengan karakteristik berbentuk tes objektif pilihan ganda yang memiliki empat pilihan jawaban dengan satu pilihan jawaban benar dan pilihan jawaban lainnya merupakan jawaban salah. Pilihan jawaban produk dikembangkan berdasarkkan jawaban subjek uji coba menggunakan soal uraian yang telah telah dilakukan sebelum produk dikembangkan. Produk yang dikembangkan memiliki kuantitas indikator dan subjek penelitian masing-masing 44,4 % dan 53,6% lebih banyak dibandingkan dengan penelitian sebelumnya.Instrumen FIDTI layak digunakan untuk mendeteksi miskonsepsi peserta didik dengan skor uji validitas sebesar 3,6 dari skor 4. Adapun diagnosis konsepsi produk pada penelitian pengembangan ini menggunakan dua kriteria. Setelah dilakukan analisis hasil uji coba produk diperoleh tingkat rata-rata persentase keakuratan keakuratan diagnosis secara keseluruhan dengan menggunakan kriteria pertama dan kedua masing-masing sebesar 73,8% dan 68,9%.